Prevalence of transfusion-transmitted infections in multiple blood transfusion-dependent thalassemic patients in Asia: A systemic review. (20th April 2022) - Riaz, Muhammad; Abbas, Mazhar; Rasool, Ghulam; Baig, Ibrahim Salam; Mahmood, Zahed; Munir, Naveed; Mahmood Tahir, Imtiaz; Ali Shah, Syed Muhammad; Akram, Muhammad
Background: Thalassemia is a hereditary hemolytic anemia marked by a defect in synthesizing one or more globin chains in hemoglobin. In Pakistan, approximately 10, 000 patients with thalassemia are primarily dependent on blood transfusions. The β-thalassemia patients require blood transfusions and iron chelation therapy. Patients who need blood transfusions are at an increased risk of contracting transfusion-transmitted infections (TTIs) such as hepatitis B and C viruses (HBV and HCV, respectively), as well as the human immunodeficiency virus (HIV). Objective: This systemic review aims to assess the prevalence of TTIs in transfusion-dependent β-thalassemia patients in Asia. Methods: The data for the systematic review were gathered from PubMed, Google Scholar, the Directory of Open Access Journals (DOAJ), and ScienceDirect using the following keywords: "prevalence, HBV, HCV, HIV, thalassemia, and transfusion-transmitted infections (TTIs), " and so on. This review includes the research articles that address the prevalence of viral infections in thalassemic patients following blood transfusion. Results: A preliminary search of various databases identified 231 potential studies. 157 duplicate studies were eliminated, and the eligibility of 59 full-length articles was determined. Only 43 studies met the inclusion criteria. Among the 43 studies analyzed, 11 reported a high prevalence of HCV alone in thalassemic patients, while 21 reported a high prevalence of HCV and HBV infection in thalassemic patients. Eight studies reported the prevalence of all three TTIs examined, namely, HCV, HBV, and HIV, in patients with transfusion-dependent thalassemia. Conclusion: Preventable transfusion-transmitted infections occur frequently, and robust national policies and hemovigilance are required to detect and mitigate the infection risk.